Electrical Impedance Tomography Predicts Weaning Success in Adult Patients With Delayed Upper Abdominal Surgery: A Single-Center Retrospective Study - Li, Jiajia; Zeng, Fan; Yang, Fuxun; Luo, Xiaoxiu; Liu, Rongan; Ren, Yinjie; Lan, Yunping; Lei, Yu; Zhao, Gaoping; Huang, Xiaobo (Frontiers in Medicine, 2021)
Abstract Objective: To evaluate the predictive value of electrical impedance tomography (EIT) in patients with delayed ventilator withdrawal after upper abdominal surgery. Methods: We retrospectively analyzed data of patients who were ventilated > 24 h after upper abdominal surgery between January 2018 and August 2019. The patients were divided into successful (group S) and failed (group F) weaning groups. EIT recordings were obtained at 0, 5, 15, and 30 min of spontaneous breathing trials (SBTs) with SBT at 0 min set as baseline.We assessed the change in delta end-expiratory lung impedance and tidal volume ratio (ΔEELI/VT) from baseline, the change in compliance change percentage variation (|Δ(CW-CL)| from baseline, the standard deviation of regional ventilation delay index (RVDSD), and global inhomogeneity (GI) using generalized estimation equation analyses. Receiver operating characteristic curve analyses were performed to evaluate the predictive value of parameters indicating weaning success.Results: Among the 32 included patients, ventilation weaning was successful in 23 patients but failed in nine. Generalized estimation equation analysis showed that compared with group F, the ΔEELI/VT was lower, and the GI, RVDSD, and (|Δ(CW-CL)|were higher in group S. For predicting withdrawal failure, the areas under the curve of the ΔEELI/VT，(|Δ(CW-CL)|, and the RVDSD were 0.819, 0.918, and 0.918 and 0.816, 0.884, and 0.918 at 15 and 30 min during the SBTs, respectively. Conclusion: The electrical impedance tomography may predict the success rate of ventilator weaning in patients with delayed ventilator withdrawal after upper abdominal surgery.